Transient control improvement on pneumatic servoing in robot system using fractional-order PID with finite-time prescribed performance control - Mohd Iskandar Putra, Azahar; Addie Irawan, Hashim; Mohd Syakirin, Ramli (IEEE, 2022)
This paper presents an effective control strategy for an industrial robot's tri-finger pneumatic gripper (TPG) that incorporates with a finite-time prescribed performance control (FT-PPC) with a fractional-order proportional-integral-derivative (FOPID) controller named as FTPPC-FOPID controller. The experiments were carried out with step input trajectories as a fundamental critical input for pneumatic rod-piston on the TPG unit. The results show that, the proposed FTPPC-FOPID controller as compared to the FOPID controller alone has improved the PPVDC rod-piston positioning performances by eliminating the oscillation on the transient response, thus avoiding overshoot, and providing fast settling time as well as steady-state error. Moreover, the proposed control strategy has improved the PPVDC's piston’s pressures with minimum control input oscillation. Overall results show that the proposed FTPPC can improve the feedback controller such as FOPID in controlling a very nonlinear system such as pneumatic servo system in TPG.